Decrease in phase angle after Roux-en-Y gastric bypass is related to increase of anti-inflammatory status - Amanda Cristina Araújo Gomes; Amanda Machado Fiorotti; Amanda Motta de Bortoli; Beatriz Bobbio de Brito; João Arthur Souza Fiorido; Luciane Bresciani Salaroli; Andressa Bolsoni Lopes; Fabiano Kenji Haraguchi (Clinical Nutrition Open Science)
Summary: Background & Aims: Phase angle (PhA) has been used as a prognostic indicator in various clinical conditions. However, its relationship with inflammatory state during obesity treatment is less known. This study investigated the relationship between PhA and inflammatory parameters in patients undergoing Roux-en-Y gastric bypass (RYGB). Methods: This is a prospective longitudinal study with patients from the Bariatric and Metabolic Surgery Program of a university hospital. Analyses were conducted pre-RYGB and about two and six months post-RYGB. Assessments included serum levels of alpha-1-acid glycoprotein (AGP), C-reactive protein (CRP), tumor necrosis factor-alpha (TNF-α), adiponectin, and resistin, as well as anthropometric data and body composition. Data were analyzed using the one-way repeated measures ANOVA or Friedman's test, followed by Tukey's post hoc test. Relationship between PhA and biochemical and body parameters were assessed using the Spearman or Pearson correlation coefficient. A significance level of 5% was adopted. Results: Final sample was composed of 23 subjects (87% women), aged 40.6 ± 10.7 years. A significant decrease in PhA values accompanied by an improvement in inflammatory parameters were observed post-RYGB (p<0.05). PhA values was inversely correlated with serum adiponectin concentrations (r= −0.376, p<0.05). In addition, BMI and fat-mass were also significantly correlated with serum adiponectin (r= −0.264 for BMI and r= −0.277 for fat-mass, p<0.05) and TNF-alpha (r= 0.338 for BMI and r= 0.335 for fat-mass, p<0.05), whereas serum resistin was correlated only with fat-mass (r= 0.245, p<0.05). Conclusions: Data suggest that the decrease in PhA values during six months post-RYGB may indicate a concomitant improvement of anti-inflammatory state.